2012
DOI: 10.2174/1874336601205010042
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory Behavior of Red Sea Urchin Strongylocentrotus Fran-ciscanus (Agassiz, 1863) and Purple Sea Urchin Strongylocentrotus Purpu-ratus (Stimpson, 1857) (Echinodermata: Echinoidea)

Abstract: Thermoregulatory behavior of red sea urchin Strongylocentrotus franciscanus and purple sea urchin S. purpuratus was determined in a horizontal thermal gradient. The preferred temperature select by the red sea urchin was 17.5 ± 0.3 ºC during the diurnal cycle and 16.8 ± 0.4 ºC for the night. The purple sea urchin preferred temperature during daytime of 18.8 ± 0.2 ºC and night was 17.4 ± 0.3 ºC. For both species of sea urchin preferendum between day and night cycles were different (P < 0.05), the purple sea urch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The temperature has been shown to have direct effects on red sea urchin metabolic rates, with an increase in oxygen consumption as temperature increases, suggesting a temperature-dependent metabolism (Ulbricht and Pritchard, 1972). It has also been suggested that red sea urchins may display different temperature preferences between day and night, moving away from unfavorable physiological temperatures (Salas et al, 2012). These thermal effects have also been observed in red sea urchin embryos, where high temperatures increased the body size of prism-stage embryos, suggesting that moderate warming may improve the growth and thermal tolerance of red sea urchins (Wong and Hofmann, 2020).…”
Section: Temporal Effectsmentioning
confidence: 99%
“…The temperature has been shown to have direct effects on red sea urchin metabolic rates, with an increase in oxygen consumption as temperature increases, suggesting a temperature-dependent metabolism (Ulbricht and Pritchard, 1972). It has also been suggested that red sea urchins may display different temperature preferences between day and night, moving away from unfavorable physiological temperatures (Salas et al, 2012). These thermal effects have also been observed in red sea urchin embryos, where high temperatures increased the body size of prism-stage embryos, suggesting that moderate warming may improve the growth and thermal tolerance of red sea urchins (Wong and Hofmann, 2020).…”
Section: Temporal Effectsmentioning
confidence: 99%